Telecommunications in select countries : policies - statistics - Telecom Regulatory Authority of India (New Delhi: TRAI, 2018)
The compilation is presented in four chapters. Chapter one contains the information and statistics on key telecom indicator related to Subscribers, Tele-density, etc. in select twenty three countries including India for the last four years ending December 2016. Chapter two covers the quality of telecom serves across the twenty three countries. Chapter three covers the the practice followed by thirteen countries for spectrum management. And chapter four contains the financials results of twenty five leading telecom companies for the last four years (including two Indian telecom companies viz. Bharti Airtel Limited and Idea Cellular Limited) operating in the selected twenty three countries. The annual financial results of these companies represent the group financials i.e, results on consolidated basis, which include operations in their country of incorporation as well as in other countries through subsidary companies/joint ventures.
Introduction -- Chapter 1. Key Performance Indicators -- Chapter 2. Telecom Quality of service in Selected Countries -- Chapter 3. International Practices of Spectrum Management -- Chapter 4. Financial Results of Leading Telecom Companies -- Annexures.
Keywords: TRAI; Telecom Regulatory Authority of India; Telecom Indicators; Telecom Service; Spectrum Management